2008
DOI: 10.1182/blood-2007-07-099465
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular endothelial cells express a phosphatidylserine receptor: a functionally active receptor for phosphatidylserine-positive erythrocytes

Abstract: Phosphatidylserine (PS)-positive erythrocytes adhere to endothelium and subendothelial matrix components. While thrombospondin mediates these interactions, it is unknown whether PSassociated erythrocyte-endothelial adhesion occurs in the absence of plasma ligands. Using ionophore-treated PSexpressing control HbAA erythrocytes, we demonstrate that PS-positive erythrocytes adhered to human lung microendothelial cells in the absence of plasma ligands, that this adhesion was enhanced following endothelial activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 53 publications
5
52
1
Order By: Relevance
“…RRx-001-mediated vascular normalization is thought primarily to be due to repolarization of TAMs; this repolarization leads to an inhibition of VEGF and MMP-9, two critically important mediators of TAM angiogenic potential; a reduction in VEGF and MMP-9 has been observed in immunohistochemically stained patient biopsies. In addition, because RRx-001-modified red blood cells bind to the hypoxic endothelium [28], inducing a microvascular 'traffic jam', blood flow is shunted or redistributed through the remaining and more normally functioning (i.e. less leaky, disordered and hypoxic) capillary system, akin to a vascular normalization effect, with a net gain in overall perfusion ( Figure 5(c)).…”
Section: Vascular 'Normalization' and Increased Tumor Blood Flowmentioning
confidence: 99%
“…RRx-001-mediated vascular normalization is thought primarily to be due to repolarization of TAMs; this repolarization leads to an inhibition of VEGF and MMP-9, two critically important mediators of TAM angiogenic potential; a reduction in VEGF and MMP-9 has been observed in immunohistochemically stained patient biopsies. In addition, because RRx-001-modified red blood cells bind to the hypoxic endothelium [28], inducing a microvascular 'traffic jam', blood flow is shunted or redistributed through the remaining and more normally functioning (i.e. less leaky, disordered and hypoxic) capillary system, akin to a vascular normalization effect, with a net gain in overall perfusion ( Figure 5(c)).…”
Section: Vascular 'Normalization' and Increased Tumor Blood Flowmentioning
confidence: 99%
“…It has been demonstrated that PS is a major component of this interaction in that PS can directly interact with EC features such as CD-36 and PS receptors (6,10,15,24) or bind to EC via plasma ligands such as TSP and lactadherin (33,34). This involvement of PS is also demonstrated in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Usually this anionic phospholipid is located exclusively on the inner leaflet of the RBC membrane but is translocated to the outer leaflet in hemoglobinopathies and oxidative stress states (9). The role of PS in adhesion has not been fully understood, but RBC with enhanced PS exposure have been identified to establish specific interactions with EC or the endothelial matrix via several receptors including thrombospondin, ␣ V ␤ 3 , CD36, and PS receptor (6,10,11).…”
mentioning
confidence: 99%
“…Recently, it was reported that microvascular endothelial cells interact with PS-positive RBCs and express a functional receptor for the PS-specific interaction, 30,31 indicating that PS-specific interactions occur between erythrocytes and the endothelium. Growing evidence has revealed that HSECs play an important role in the blood clearance of macromolecules and apoptotic cells.…”
Section: Hsecs Mediate Tethering Of Damaged Rbcs In a Ps-dependent Mamentioning
confidence: 99%